The Influence of Transformational Leadership Style on Work Program Achievement at GKI Bethesda Selebesolu - Tagor Manurung; Berti Pakaila (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study examines the impact of transformational leadership on work program achievement at GKI Bethesda Selebesolu in Sorong City, Papua. The church is managed by the Congregation Council (PHMJ), with leadership significantly influencing organizational effectiveness. The aim of the research is to evaluate the transformational leadership style of the PHMJ Chair and its effect on the success of the church's work programs. The study utilizes a quantitative approach with a sample of 37 respondents from the congregation, employing simple linear regression analysis to assess the relationship between transformational leadership and work program achievement. The findings reveal that transformational leadership has a significant positive impact on work program success, with 57.1% of the variance explained by leadership style. The results suggest that transformational leadership, characterized by inspiration, vision, and personal development, enhances organizational performance. The study highlights the importance of transformational leadership in religious organizations, providing insights for future leadership improvements at GKI Bethesda Selebesolu.